Job Satisfaction and Employeeâs Self-Schema at Workplace: A Literature Review - Mehrad, Aida (Journal of Educational, Health and Community Psychology, 2016)
AbstractÂ The purpose of the present study is to determine the relationship between job satisfaction and self-schema amongst employees at the workplace. The results of the study revealed that self-schema derived from feelings and attitudes of employees based on their satisfaction at the workplace; and, explained that employees schemas are various, completely.Â This study likewise considered on job satisfaction as a main organizational factor that increases the amount of performance and presence of employees at the workplace. Also, it focused on self-schema that pivotal role in employees believes about themselves. Moreover, lack of attention to job satisfaction that influenced on employees scheme appearedÂ some abnormal organizational behaviors at workplace. Thus, the present study supports job satisfaction to achieve appropriate scheme among employees at the workplace.Â Keywords: Job satisfaction, Self-Schema, Employee, WorkplaceÂ